An Etching‐Free Approach Toward Large‐Scale Light‐Emitting Metasurfaces. Issue 14 (8th April 2019) - Brière, Gauthier; Ni, Peinan; Héron, Sébastien; Chenot, Sébastien; Vézian, Stéphane; Brändli, Virginie; Damilano, Benjamin; Duboz, Jean‐Yves; Iwanaga, Masanobu; Genevet, Patrice
Abstract: A new class of quasi 2D optical components, known as metasurfaces and exhibiting exceptional optical properties have emerged in recent years. The scattering properties of their subwavelength patterns allow molding the wavefront of light in almost any desired manner. While the proof of principle is demonstrated by various approaches, only a handful of low cost and fabrication friendly materials are suitable for practical implementations. To further develop this technology toward broadband application and industrial production, new materials and new fabrication methods are required. In addition, moving from passive to active devices with, for instance, dynamic tuning requires to move from dielectrics to semiconductors. Here, an etching‐free process is presented that combines nanoimprint and selective area sublimation of a semiconductor material to realize centimeter‐scale metalenses of high optical quality. Use of gallium nitride is chosen for this demonstration, as it is a widespread semiconductor which can be transparent and active in the visible. The sublimation leads to reduced surface roughness and defects compared to reactive ion etching. As a result, the devices show enhanced photoluminescence efficiency with respect to etched devices. Amplification due to gain in the semiconductor based metaoptics could lead to a new type of optoelectronic devices. Abstract : Nanoimprinting lithography is used to realize centimeter‐scale semiconductor‐based UV metalenses. Avoiding a dry‐etching process to preserve the excellent light‐emission properties of nanoresonators, nanopatterning is realized using selective area sublimation of GaN. These results represent significant steps toward the realization of active metasurfaces.